Evaluation of the systemic toxicity and mutagenicity of OLIGOPIN®, procyanidolic oligomers (OPC) extracted from French Maritime Pine Bark extract. (2018) - Segal, L; Penman, MG; Piriou, Y
Highlights: The potential systemic toxicity and mutagenicity of Oligopin®, a French Maritime Pine Bark extract, was evaluated. Oligopin® was nongenotoxic in both bacterial and human cell assays. Oligopin® was not acutely toxic and 90 days of oral administration to rats was well tolerated with a NOAEL of 1000 mg/kg/day. The lack of adverse systemic effects in the 90 day study is concordant with findings from human clinical trials. The NOAEL from the 90-day study suggests that Oligopin® is less systemically toxic than other FMPBE evaluated in subchronic studies. Abstract: The potential systemic toxicity of Oligopin®, a French Maritime Pine Bark extract (FMPBE) rich in procyanidolic oligomers, was evaluated in an acute oral limit test and a 90-day repeated dose oral toxicity study with Sprague Dawley rats. The potential mutagenicity was assessed in a bacterial reverse mutation assay and in vitro mammalian chromosome aberration assay with human lymphocytes. The results indicate that Oligopin® was nongenotoxic in both bacterial and human cell assays, was not acutely toxic via oral administration at up to 2000 mg/kg and was well tolerated following 90 days of oral administration to SD rats, with a no observed adverse effect level of 1000 mg/kg/day. The lack of significant adverse systemic effects in the 90 day study is concordant with findings from several human clinical trials. The acute toxicity and mutagenicity data are consistent with data reported by AFSSA in a summary of FMPBE safety, in which a NOAEL of 100 mg/kg/day was established. In contrast, the NOAEL derived from the 90-day study with Oligopin® was 1000 mg/kg/day, suggesting that it is less systemically toxic than other FMPBE previously evaluated in subchronic studies, and comparable to proanthocyanidins extracted from grape seeds, which are widely used as nutritional supplement ingredients.